Kinetic analysis of the transphosphorylation with creatine kinase by pressure-assisted capillary electrophoresis/dynamic frontal analysis - Mine, Masanori; Mizuguchi, Hitoshi; Takayanagi, Toshio (Analytical and bioanalytical chemistry, 2021)
Kinetic reactions of the transphosphorylation with creatine kinase (CK) were individually investigated between creatine (Cr) and creatine phosphate (CrP) by pressure-assisted capillary electrophoresis/dynamic frontal analysis (pCE/DFA). The transphosphorylations are reversible between Cr and CrP, and reverse reactions inevitably accompany in general batch analyses. In pCE/DFA, the kinetic reaction proceeds in a separation capillary and the product is continuously resolved from the substrate zone. Therefore, the formation rate is kept constant at the substrate zone without the reverse reaction, and the product is detected as a plateau signal. This study demonstrates the direct and individual analyses of both the forward and the backward kinetic reactions with CK by pCE/DFA. A plateau signal was detected in the pCE/DFA with ADP or ATP as one of the products on either the forward or the backward reactions. The Michaelis-Menten constants of K m,ATP (from Cr to CrP) and K m,ADP (from CrP to Cr) were successfully determined through the plateau signal. Determined values of K m,ATP and K m,ADP by pCE/DFA were smaller than the ones obtained by the pre-capillary batch analyses. The results agree with the fact that the reverse reaction is excluded in the analysis of the kinetic reactions. The proposed pCE/DFA is useful on individual analyses of both forward and backward kinetic reactions without any interference from the reverse reaction.